Metformin and daclatasvir: absence of a pharmacokinetic–pharmacodynamic drug interaction in healthy volunteers. (6th June 2017) - Smolders, Elise J.; Colbers, Angela; de Kanter, Clara T. M. M.; Velthoven‐Graafland, Kirsten; Wolberink, Leonie T.; van Ewijk‐Beneken Kolmer, Noor; Drenth, Joost P. H.; Aarnoutse, Rob E.; Tack, Cees J.; Burger, David M.
Abstract : AIM: The aim of the present study was to evaluate the effect of the proposed organic cation transporter (OCT) inhibitor daclatasvir on the pharmacokinetics and pharmacodynamics of the OCT substrate metformin. METHODS: This was an open‐label, two‐period, randomized, crossover trial in 20 healthy subjects. Treatment A consisted of metformin and treatment B consisted of metformin + daclatasvir. Pharmacokinetic curves were recorded at steady‐state. Geometric mean ratios (GMRs) with 90% confidence intervals (CIs) were calculated for metformin area under the concentration–time curve from 0 h to 12 h (AUC0–12 ), maximum plasma concentration (Cmax ) and final plasma concentration (Clast ). An oral glucose tolerance test was performed, measuring insulin, glucose and lactate levels. RESULTS: The GMRs (90% CI) of metformin AUC0–12, Cmax and Clast (B vs. A) were 109% (102–116%), 108% (101–116%) and 112% (103–122%). The geometric mean AUC0–2 for insulin, glucose and lactate during treatments A and B were 84 h . mEl –1 and 90 h . mEl –1, 13.6 h . mmol l –1 and 13.4 h . mmol l –1, and 3.4 h . mmol l –1 and 3.5 h . mmol l –1, respectively. CONCLUSIONS: Bioequivalence analysis showed that daclatasvir does not influence the pharmacokinetics of metformin in healthy subjects. Pharmacodynamic parameters were also comparable between treatments.